2017
DOI: 10.1519/jsc.0000000000002070
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Model to Identify Risk of Sarcopenia and Physical Disability in HIV-Infected Patients

Abstract: Farinatti, P, Paes, L, Harris, EA, Lopes, GO, and Borges, JP. A simple model to identify risk of sarcopenia and physical disability in HIV-infected patients. J Strength Cond Res 31(9): 2542-2551, 2017-Early detection of sarcopenia might help preventing muscle loss and disability in HIV-infected patients. This study proposed a model for estimating appendicular skeletal muscle mass (ASM) to calculate indices to identify "sarcopenia" (SA) and "risk for disability due to sarcopenia" (RSA) in patients with HIV. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
8
0
3
Order By: Relevance
“…These findings underscore the hypothesis that sarcopenia in PLHIV develops earlier due to aging of the immune system, caused by chronic systemic inflammatory process, virus infection, and antiretroviral therapy. 8 …”
mentioning
confidence: 99%
“…These findings underscore the hypothesis that sarcopenia in PLHIV develops earlier due to aging of the immune system, caused by chronic systemic inflammatory process, virus infection, and antiretroviral therapy. 8 …”
mentioning
confidence: 99%
“…Regarding the skeletal mass index, a lower score was found among the smokers patients with HIV/AIDS have a loss of muscle mass typically observed in older people, probably due to a constant state of infection and long-term use of antiretroviral drugs 9,30 . Rom et al demonstrated that smokers aged over 45 years with lower appendicular skeletal muscle mass are more likely to develop sarcopenia than individuals who never smoked, regardless of sex 31 .…”
Section: Clinical Characteristics and Body Composition Total Sample Non-smoker Smoker P-valuementioning
confidence: 89%
“…Another process that is considered important among individuals with HIV/AIDS using cART is the progressive reduction of muscle mass or sarcopenia [9][10][11] . Sarcopenia is defined as the generalized loss of skeletal muscle mass, accompanied by reduced strength and functional capacity, and is considered a risk factor for incapacity and mortality in HIV-infected patients 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Também é importante observar que a força muscular no período pré-intervenção foi semelhante entre os grupos G TFRFS e G TFT , provando que a formação dos grupos de treinamento pelo ranking de 1RM, seguida pela alocação aleatória, não influenciou os resultados observados Devido a doenças que afetam a função muscular, como a caquexia e a sarcopenia, as PVHA podem apresentar TME, força muscular e capacidade funcional reduzidas (ERLANDSON et al, 2013;FARINATTI et al, 2017). O TFT demonstrou eficácia como terapia complementar no tratamento de PVHA, aumentando a TME e a força muscular (LINDEGAARD et al, 2008;VINGREN et al, 2017).…”
Section: Discussionunclassified